"How many slaves work for you?" Race, new media, and neoliberal consumer activism. (March 2017) - Page, Allison
This article analyzes the website slaveryfootprint.org, which purports to measure consumers' reliance on slave labor in the Global South by analyzing the users' consumption habits. The site offers neoliberal consumer solutions to "solve" the problem of what it terms modern-day slavery. I argue that the characterization of slavery on slaveryfootprint.org (and the process of de-fetishizing this labor) attempts to shore up a distinction between "free" and forced labor, but unwittingly illuminates the ambiguity of this divide. By understanding slavery as embedded in capitalism, I suggest that we can challenge slaveryfootprint.org's distinction between "free" labor and slavery, and in the process, the notion of "ethical" consumption.